1988
DOI: 10.1126/science.3264419
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hepatitis Induced by α 1 -Antitrypsin: a Transgenic Mouse Model

Abstract: Transgenic mouse lineages were established that carry the normal (M) or mutant (Z) alleles of the human alpha 1-antitrypsin (alpha 1-Pi) gene. All of the alpha 1-Pi transgenic mice expressed the human protein in the liver, cartilage, gut, kidneys, lymphoid macrophages, and thymus. The human M-allele protein was secreted normally into the serum. However, the human Z-allele protein accumulated in several cell types, but particularly in hepatocytes, and was found in serum in tenfold lower concentrations than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(63 citation statements)
references
References 12 publications
2
61
0
Order By: Relevance
“…The proteasome may initiate a process which is completed by other enzymes within tion in the neonatal period. 9 There are also nodular clusters of altered hepatocytes that lack a 1 -AT-immunoreactivity the ER membrane or within the ER lumen.…”
Section: Mechanism Of Liver Cell Injurymentioning
confidence: 99%
“…The proteasome may initiate a process which is completed by other enzymes within tion in the neonatal period. 9 There are also nodular clusters of altered hepatocytes that lack a 1 -AT-immunoreactivity the ER membrane or within the ER lumen.…”
Section: Mechanism Of Liver Cell Injurymentioning
confidence: 99%
“…The strongest evidence for the gain-of-toxic function mechanism is the development of liver disease in mice transgenic for mutant human ␣1ATZ. 3,5 Because normal levels of endogenously derived anti-elastases are present in these mice, the liver injury cannot be attributed to a loss-of-function mechanism.…”
Section: Mechanisms Of Target Organ Injury In ␣1at Deficiencymentioning
confidence: 99%
“…1). Studies of the Z#2 mouse model, generated by using a human ␣1ATZ genomic fragment as transgene, 3 have shown that these globuledevoid cells occupy an increasing proportion of the liver as the animal ages and ultimately become the site of adenomas and carcinomas. 4 In more recent studies using the PiZ mouse model, another transgenic mouse created with a human ␣1ATZ genomic fragment, 5 we have shown that there is increased proliferation of these globule-devoid hepatocytes at a rate that is directly proportional to the number of globule-containing hepatocytes.…”
mentioning
confidence: 99%
“…The most compelling evidence for the gain-of-toxic function mechanism comes from the observation that mice transgenic for the mutant human ATZ gene develop hepatic inflammation and carcinomas together with the characteristic intrahepatocytic globules. 10,11 These mice have normal levels of endogenous anti-proteases and so the liver disease must be attributable to a gain-of-toxic function mechanism.…”
mentioning
confidence: 99%